Efficacy and safety of endothelin receptor antagonists in type 2 diabetic kidney disease: A systematic review and meta‐analysis of randomized controlled trials. Issue 1 (9th October 2020) - Zhou, Y.; Chi, J.; Huang, Y.; Dong, B.; Lv, W.; Wang, Y. G.
Abstract: Aim: To analyse the efficacy and safety of endothelin receptor antagonists for people with diabetic kidney disease. Methods: Randomized controlled trials comparing endothelin receptor antagonists with placebo in people with diabetic kidney disease were identified through PubMed, Embase and the Cochrane Library. We used a random‐effect model to calculate the mean difference or risk ratio with the 95% CI. Results: Seven studies with a total of 4730 participants were included. Overall, endothelin receptor antagonists significantly reduced albuminuria compared with placebo (standardized mean difference –0.48, 95% CI –0.64 to –0.33). Atrasentan, in particular, effectively reduced albuminuria (standardized mean difference –0.58, 95% CI –1.00 to –0.17) and the risk of composite renal endpoints (risk ratio 0.65; 95% CI 0.49 to 0.88), with insignificant change in the rate of congestive heart failure (risk ratio 1.40, 95% CI 0.76 to 2.56) and mortality (risk ratio 1.11, 95% CI 0.77 to 1.61). In contrast, although avosentan reduced albuminuria (standardized mean difference –0.47, 95% CI –0.57 to –0.36) and the risk of composite renal endpoints (risk ratio 0.63, 95% CI 0.42 to 0.94), it was associated with a significant increase in congestive heart failure risk (risk ratio 2.61, 95% CI 1.36 to 5.00) and an insignificant increase in mortality risk (risk ratio 1.50, 95% CI 0.81, 2.78). No significant change in efficacy or safety outcomes with bosentan was detected. Dose–response analysis indicated that 0.75 mg/day atrasentan is expected to be optimal for renoprotection, with maximal albuminuria reduction and minimal fluid retention events. Conclusions: Among the endothelin receptor antagonists, atrasentan and avosentan, but not bosentan, are effective for renoprotection in people with diabetic kidney disease. Compared with other types and doses, atrasentan 0.75 mg/day is the most promising, with maximal albuminuria reduction and minimal fluid retention. Vigilant monitoring of congestive heart failure risk is needed in future clinical practice. (PROSPERO registration no. CRD42020169840).